2018
DOI: 10.1016/j.jneumeth.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

High channel count microphone array accurately and precisely localizes ultrasonic signals from freely-moving mice

Abstract: These changes facilitated the acquisition of larger and more comprehensive data sets that better represent the vocal activity within an experiment. Furthermore, this system will allow more thorough analyses of the role that vocal signals play in social communication. We expect that such advances will broaden our understanding of social communication deficits in mouse models of neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 56 publications
7
39
0
Order By: Relevance
“…A sound source localization system was used to assign vocal signals to individual mice 47 . For each signal, the system computed eight individual estimates of where the sound originated.…”
Section: Sound Source Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A sound source localization system was used to assign vocal signals to individual mice 47 . For each signal, the system computed eight individual estimates of where the sound originated.…”
Section: Sound Source Localizationmentioning
confidence: 99%
“…Therefore, to overcome this issue, we have implemented an eight-channel microphone array system 47 , allowing us to localize the source of ultrasonic vocal signals. This technology, in conjunction with video tracking software 48 , allows us to track the social and vocal behavior of individual animals over time.…”
mentioning
confidence: 99%
“…Specific phases of courtship interactions trigger different call types (Hanson and Hurley, 2012;Nyby, 1983). Triangulation has been used to determine the emitter of the USVs (Warren et al, 2018a). In a group of four adult mice (two males and two females, aged 3-5 months)…”
Section: Introductionmentioning
confidence: 99%
“…While Neunuebel et al [ 20 ] showed that female mice vocalize when males are present, a systematic comparison between vocalizations emitted by males and females as the animals were freely interacting was never conducted. Consequently, we employed an eight-channel microphone array [ 36 ] to track vocal behavior of individual mice ( Mus Musculus ) during unrestrained opposite-sex dyadic interactions and directly compared the vocal activity of males and females across specific behavioral contexts.…”
Section: Introductionmentioning
confidence: 99%